An agent on my shoulder: AI, privacy and the application of human-like computing technologies to music creation - Chamberlain, Alan; Malizia, Alessio; De Roure, David (2017)
Human-Like Computing technologies are intelligent systems that interact with people in human-like way. By bringing together the disciplines of Artificial Intelligence, Ethnography and Interaction Design, and applying them in a real world context we are able to understand some of the ways that such technologies can be applied. This work in progress poster applies such technologies to the music creation and develops a design that is based on the notion of an ‘Intelligent’ Agent that is able to support in the music creation process.